Marital Property in Marriages of Different Nationalities in Indonesia According to National Law and Islamic Law - Maula, Bani Syarif; Zain, Muhammad Fuad; Nada, Syifaun (Jurnal Syariah dan Hukum Komparatif, 2024)
Indonesian legislation stipulates that individuals from foreign countries residing in Indonesia and foreign legal entities with representatives in the country are expressly barred from possessing land. This provision poses challenges for individuals in marriages involving different nationalities, particularly when one spouse is an Indonesian citizen, as it complicates the process of acquiring ownership rights and building usage rights for a property. This research explores the legal regulations pertaining to marital property in marriages involving individuals of distinct nationalities, navigating the intersection between national law and Islamic law. Employing qualitative research methods with a normative approach, the study relies on legal materials as primary data sources. The findings of this study indicate that, in accordance with national law, assets acquired during the course of marriage are deemed joint property. Nonetheless, it is noteworthy that this provision does not extend to marital assets in the form of land and buildings for foreign spouses. Conversely, Islamic law does not explicitly delve into this matter. Nevertheless, it delineates that the resolution of joint property in marriages encompassing individuals of diverse nationalities is governed by national laws pertaining to citizenship rights. In the case of foreign citizens, the relevant statute is the Agrarian Law, which specifically governs ownership rights concerning land and buildings.